What makes an animal? The molecular quest for the origin of the Animal Kingdom - Paps, J (Oxford University Press, 2018)
What makes an animal? To find the answer we need to integrate data from disciplines such as phylogenetics, paleontology, ecology, development, anatomy, and physiology, as well as molecular biology and genomics. Knowledge of which groups branched before and after the origin of animals is essential. Recent advances in molecular phylogenetics, together with the discovery of new eukaryotic lineages, have drawn a new picture of the ancestry of animals. The nature of the early diverging animal lineages and the timing of the transition are in a state of flux. Various factors have been linked to this striking transition to multicellularity, including changes in environmental conditions and the ecological interactions between unicellular eukaryotes. The current wealth of genomic data has also shed new light on this question. The analysis of the genome of various close relatives of animals has revealed the importance that recycling of ancient genes into metazoan biological functions played into animal origins. A recent study reconstructing the genome of the last common ancestor of extant animals has unveiled an unprecedented emergence of new genes, highlighting the role of genomic novelty in the origin of metazoans.